Malignant biphasic uterine tumours: carcinosarcomas or metaplastic carcinomas? - McCluggage, W G (Copyright 2002 Journal of Clinical Pathology, 2002)
Uterine carcinosarcomas (malignant mixed Mullerian tumours) are highly aggressive and have traditionally been regarded as a subtype of uterine sarcoma. However, in recent years convincing evidence has suggested that most, but not all, are monoclonal in origin rather than true collision tumours. Data confirm that the carcinomatous element is the “driving force” and that the sarcomatous component is derived from the carcinoma or from a stem cell that undergoes divergent differentiation. Thus, uterine carcinosarcomas are best regarded as metaplastic carcinomas, although the designation carcinosarcoma is likely to remain. Adjuvant treatment for uterine carcinosarcoma should probably be similar to that directed against aggressive high grade endometrial carcinomas rather than being sarcoma based. Importantly, a small proportion of uterine carcinosarcomas are true collision tumours and should be recognised as such because, in some instances, the prognosis may be better than for a similar stage carcinosarcoma.